The effect of a training curriculum using variable resistances according to performance on the momentary strength and achievement of the junior long jump (Journal of the College of Basic Education, 2022)
The research problem lies in many reasons, including weakness in the physical variables, especially speed and muscular strength, whether it is explosive or a force distinguished by speed, and for this particular age stage, and the importance of these variables for long jump players (juniors), so the researcher tries to resort to using exercises to develop momentary strength in this Effectiveness and for these ages, which helps in diagnosing weaknesses during performance and trying to avoid them through the use of a training curriculum that includes exercises to develop momentary strength and identifying their impact, which may work to help jumpers in training in the right direction, and then develop in performance and achieve the best achievement,